USING THE REACT LEARNING MODEL TO REDUCE STUDENT ANXIETY IN LEARNING MATHEMATICS - Sitorus, Martina Srimega; Saragih, Melda Jaya (Universitas Pelita Harapan, 2023)
Mathematical anxiety is an emotional response to the entire mathematical activity that affects students' mathematical to psychological abilities. This anxiety is influenced by various factors, such as negative perspectives on mathematics, experiences of failing in learning mathematics, and others. Research data at one Christian High School in Tangerang shows that class X social studies students experience mathematical anxiety where students have difficulty concentrating, are restless, unconfident, and have headaches when learning mathematics. Anxiety affects students' self-confidence and makes the learning process not optimal, so it needs to be reduced. The selection of the REACT model as a solution to this problem leads to varied, contextual, and collaborative learning. The purpose of this writing is to find out the application of the REACT model in reducing the mathematical anxiety of X social studies students. The method used in the research is descriptive qualitative, where data is collected through questionnaires. The results show that the REACT model stages, namely relating, experiencing, applying, cooperating, and transferring, succeeded in reducing the anxiety of class X social studies students towards learning mathematics. During the application of the model, students are seen concentrating while studying, having confidence, daring to ask questions, and others. Applying the REACT model can be a solution for teachers to manage mathematical anxiety while leading students to realize their identity as imago dei who have been reconciled to God in Jesus Christ. Students are endowed with a Divine capacity to do God's work. Reflecting on the implementation of the REACT model, the author suggests recognizing the characteristics of each student the characteristics and collaborating the REACT model with other learning resources.